Long-term tillage impact on soil phosphorus under different crop sequences - Giannini, Ana Paula; Andriulo, Adrian Enrique; Wyngaard, Nicolás; Irizar, Alicia Beatriz (Wiley, 2024)
Management practices, such as tillage and cropping diversification, influence soil phosphorus (P) dynamics. The aim was to evaluate the long-term effect of tillage systems (no tillage, NT; vertical tillage, VT; conventional tillage, CT) on total (TP) and extractable (Pe) soil P distribution under different crop sequences (corn–wheat/soybean, C–W/S; wheat/soybean, W/S; corn–corn, C–C; soybean–soybean, S–S). TP and Pe were measured up to 50 cm deep. The TP distribution was associated to soil organic carbon (SOC) (r = .89, p < .01) and tend to increase near soil surface under NT as compared with CT and VT. The Pe was sensitive to the crop residues pattern of accumulation and their quality in the topsoil. Crop sequences that included corn had lower Pe concentration under NT. Conversely, in W/S, Pe concentration was lower under VT with no differences between NT and CT and, in S–S sequence, there were no differences in Pe concentration. However, under NT the increase in the above-ground biomass in sequences without corn (p < .001) increased Pe concentration in 0–5 cm layer, while the opposite occurs in sequences with corn (p < .06). In S–S under NT, the low crop residue input (1.6 Mg of dry matter ha−1) and the high Pe concentration in 0–5 cm layer (40 mg kg−1) might increase the risk of P loss to adjacent ecosystems. Intensified sequences presented more negative P balances than corn/soybean monoculture. This study demonstrates that it's necessary to develop management strategies that improve P supply in synchrony with the crop demand and decrease P loss, while keeping productivity.